Editorial - Nain, Manjeet Singh (Indian Journal of Extension Education, 2025)
The pandemic brought forward the new calling for a more sustainable food supply and sustainable eating in the minds of consumers. Environmental sustainability continues to climb, which demand focus on technology, partnering and institutional reform. It’s my privilege to present the current issue (July-September, 2021) from cross sectional authors and content ranging from basic research in the form of measuring tool development; consumer perception analysis;, maternal and child health issues; promising avenues like DSR, contract farming, value chain mapping, water conservation; climate change; knowledge about different dimensions of current pandemic; agro tourism; information sources including traditional, ICTs as well as OTT; core competencies of extension system as well as education system; social dimensions of animal husbandry; livelihood security analysis; geography and crop specific constraints analysis; adoption status and so on. Its more satisfying that authors have reoriented their research issues in light of current situations. The scientific reporting need far deeper commitment and more active engagement, I am happy that the readers, authors and reviewers have significantly contributed towards successful implementation. Again, it is appealed for more active involvement of each stakeholder in the endeavour. We, at Indian Journal of Extension Education (IJEE) level are fully open access through online submission and management of all content. The IJEE is now indexed at CAB International; metadata in desirable form is being submitted to Crossref to have wider circulation and opportunity for citations and indexing. I extend my sincere thanks to all the authors for making valuable contributions. I also extend sincere thanks to all the expert members in the editorial board for their painstaking efforts. The support extended by Executive Council is duly acknowledged. Special thanks are extended to the President, ISEE; Dr. U.S. Gautam, Secretary ISEE; Dr. Rashmi Singh, Treasurer, ISEE; Dr. B. K. Singh and Joint Secretary, ISEE; Dr. J. S. Malik for providing insightful thoughts and guidance in bringing out this issue. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters.